Primary Aneurysm of the Medial Marginal Vein of the Foot - D. Casian; V. Culiuc (Case Reports in Vascular Medicine)
The primary superficial venous aneurysms of the foot are very rare. A 34-year-old female patient developed a dorsal foot mass during the second trimester of pregnancy with no history of previous trauma, puncture, or infection. One year later, she was referred to the surgical department for excision of “foot hygroma.” Based on the clinical findings, the venous aneurysm was suspected and duplex ultrasound confirmed the diagnosis of the aneurysm of the medial marginal vein of the foot. Excision of aneurysm with bipolar ligation of marginal vein was performed under local anesthesia. The postoperative evolution was uneventful. The authors hope that the presented case report will increase the awareness of general practitioners, dermatologists, and surgeons regarding the superficial venous aneurysms of lower limbs.